PENGARUH KARAKTERISTIK CEO TERHADAP PENGUNGKAPAN INFORMASI ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) - Agus Triyani; Suhita Whini Setyahuni (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2020)
This study intends to examine the effect of CEO characteristics on environmental, social, and governance (ESG) disclosure. We took sample by using pusposive technique in public listed companies in Indonesia during 2012-2017 periods. A total of 159 firms-years observations were included in the sample. The results indicate that CEO’s tenure and CEO’s age impact ESG disclosure negatively, while educational background impact ESG disclosure positively. Our findings provide new evidence on the role of CEO on companies’s sustainability performance. The findings are expected to be able to ensure the importance of choosing the right CEO’s characteristics in order to enhance ESG disclosure.